Stanisław Kalinkowski, Jerzy Andrzej Wojtczak-Szyszkowski, Iure et legibus. Język łaciński dla studentów prawa, Warszawa 2000, Wyższa Szkoła Handlu i Prawa im. R. Łazarskiego, ss. 232. - Pokrywka, Władysław (Vox Patrum, 2000)
review